Dissident: Oswaldo Paya and the Varela Project - Ewing, Heidi (United States : Loki Films, 2003)
The 20-minute documentary portrays a grassroots pro-democracy movement -- the Varela Project -- struggling to peacefully advance human and political rights in Cuba. Oswaldo Payá Sardiñas, leader of the movement, shares his uncensored story of this civic campaign, which calls for a referendum on open elections, freedom of speech, freedom for political prisoners and free enterprise.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films